What do female nursing students know about osteoporosis: A survey study: Nursing students’ osteoporosis knowledge and affecting factors - Kalkim, Asli; Daghan, Safak (Progress in Nutrition, 2018)
Aim: The aim of the study was to examine female nursing students’ knowledge of osteoporosis and its affecting factors. Methods: This is a descriptive survey conducted in the faculty of nursing of a state university in the west of Turkey. The sample of the study consisted of 701 female students. A nursing student information form and the Revised Osteoporosis Knowledge Test were used to collect the data. Results: Most of the students had heard of osteoporosis but they had inadequate knowledge. The multiple regression analysis showed that being a third or fourth year student and obtaining information on osteoporosis from the internet accounted for 13% of the nursing students’ knowledge of osteoporosis. Conclusion: Nurses take on responsibilities for the prevention and early diagnosis of osteoporosis. For this reason, it is of the utmost importance for students, who are the nurses of the future, to fill the gaps in the knowledge which they will feel the need of in helping at-risk groups in society to gain information, awareness and preventive behaviors with regard to osteoporosis.